Correlation of cognitive ability relevance to the ability of scientific creative thinking and scientific critical thinking skills of students of work and energy concept - H Rusnayati; R Wulansari; D Saepuzaman; S Karim; S Feranie A (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The aim of this study was to analyze the correlation of cognitive ability relationshipto the ability of scientific creative thinking and students' critical scientific thinking ability.Research method used is correlation research because in this research there is no effort toinfluence the research variables. Participants are high school students in Cimahi cityconsisting of 32 students. Cognitive tests are sorted by sub-chapter on work and energy anddivided into four cognitive levels ranging from C1 to C4. Scientific thinking thinking tests arebased on the Scientific Structure Creativity Model (SSCM) with three assessed abilities offluency, flexibility and originality. While the critical thinking test instruments are based on theAssessment of Critical Thinking Ablility (ACTA) with the three capabilities being reviewed:Critical Thinking Ability 1, Critical Thinking Ability 2 and Critical Thinking Ablility 3.Correlation coefficient value for the relationship of cognitive ability with creative thinkingability is 0.743578, the correlation coefficient value for the relationship of cognitive abilitywith critical thinking ability is 0, 745445there is a very strong relationship between the abilityof creative thinking and critical thinking ability with cognitive ability.